2019
DOI: 10.1001/jamapediatrics.2018.3101
|View full text |Cite
|
Sign up to set email alerts
|

Association of Prenatal Exposure to Air Pollution With Autism Spectrum Disorder

Abstract: IMPORTANCEThe etiology of autism spectrum disorder (ASD) is poorly understood, but prior studies suggest associations with airborne pollutants.OBJECTIVE To evaluate the association between prenatal exposures to airborne pollutants and ASD in a large population-based cohort. DESIGN, SETTING, AND PARTICIPANTSThis population-based cohort encompassed nearly all births in Metro Vancouver, British Columbia, Canada, from 2004 through 2009, with follow-up through 2014. Children were diagnosed with ASD using a standard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(55 citation statements)
references
References 32 publications
2
50
1
Order By: Relevance
“…In the most recent one, a total of 25 studies were investigated to analyze the role of maternal exposure to air pollution and risk of autism spectrum disorders in children, resulting in ORs of 1.06 (95% CI 1.01–1.11) for PM2.5 and 1.02 (95% CI 1.01–1.04) for NO 2 [ 96 ]. In a large Canadian cohort of 132,256 births, maternal exposure to NO was associated with increased risk of development of autism spectrum disorders in children (OR 1.07, 95% CI 1.01–1.13 per IQR increase), whereas associations were less pronounced (or only showed a trend) for PM2.5 (OR 1.04, 95% CI 0.98–1.10) and NO 2 (OR 1.06, 95% CI 0.99–1.12) [ 97 ]. Interestingly, a recent study in the US has shown that gestational diabetes mellitus and maternal exposure to O 3 were associated with additive effects on autism risk, likely due to shared pathways that include inflammation and oxidative stress [ 98 ].…”
Section: Evidence From Human and Animal Studiesmentioning
confidence: 99%
“…In the most recent one, a total of 25 studies were investigated to analyze the role of maternal exposure to air pollution and risk of autism spectrum disorders in children, resulting in ORs of 1.06 (95% CI 1.01–1.11) for PM2.5 and 1.02 (95% CI 1.01–1.04) for NO 2 [ 96 ]. In a large Canadian cohort of 132,256 births, maternal exposure to NO was associated with increased risk of development of autism spectrum disorders in children (OR 1.07, 95% CI 1.01–1.13 per IQR increase), whereas associations were less pronounced (or only showed a trend) for PM2.5 (OR 1.04, 95% CI 0.98–1.10) and NO 2 (OR 1.06, 95% CI 0.99–1.12) [ 97 ]. Interestingly, a recent study in the US has shown that gestational diabetes mellitus and maternal exposure to O 3 were associated with additive effects on autism risk, likely due to shared pathways that include inflammation and oxidative stress [ 98 ].…”
Section: Evidence From Human and Animal Studiesmentioning
confidence: 99%
“…Recently, in a Canadian population-based birth cohort, a significant association between exposure to nitric oxide and ASD was found. No association was found between ASD and particulate matter with a diameter of <2.5 μm or nitrogen dioxide [74]. These contradictory results might be due to the fact that studies of air pollution have been often limited by indirect and cross-sectional methods of exposure measurement, by different metrics of exposure, by different evaluations of outcomes, and by focusing on different pollutants.…”
Section: Prenatal Periodmentioning
confidence: 99%
“…Metallothioneins (MT) are intracellular proteins involved in the homeostasis of essential metals and the detoxification of heavy metals (100). The consequences of environmental exposure to noxious agents and their exact role in the pathology of ASD are still under investigation, but it is known that exposure to pollution and heavy metals is causally implicated in changes of fetal neurodevelopment that are related with autism (8, 101, 102). The presence of anti-MT antibodies has been described in metal-induced diseases such as occupational heavy metal exposure and metal allergy (103, 104).…”
Section: Autoantibodies In Asd Patientsmentioning
confidence: 99%